The construction of the leader - Pereyra Lavandina, Mario (2012)
In these new hypermodern times the figure of the leader is characterized byconvey a successful image amid the applause and the crowd cheers. However,very different are the leaders that display the sacred history of the bible. Withintheir context a remarkable character appears with his weakness and failures andonly God’s grace helps overcome the adversity and incarnating lofty values thatconstitute existing models always. In this paper we analyze different perspectiveson biblical leaders regarding the singular figure of Judah, the fourth son of thepatriarch Jacob founder of Israel.